OpenBio-2021 chips: foodtech, Scopus and countering viruses - article Editorial (Разработка и регистрация лекарственных средств, 2021)
From October 5 to 8, the international scientific congress in the field of biotechnology, virology and biopharmaceuticals OpenBio will take place in the Koltsovo science city of the Novosibirsk region. Traditionally, a scientific conference and a business forum will be held within its framework. The event will be organized in a hybrid format: experts, speakers and guests can participate online.